Review of NIDA for Teens. Issue 4 (2nd October 2018) - Phillips, Kat
Abstract: Teenagers are faced with the task of navigating a world of peer pressure surrounding drug and alcohol use, and an internet filled with more information than any human could process in a lifetime. This column discusses the solid consumer health resource, NIDA for Teens, where teenagers, their parents, and their teachers can be directed in order to find science-based facts and answers to many of their pressing questions.